Influence of oxygen flow on crystallization and morphology of PLZT thin films - Simoes, A. Z.; Gonzalez, AHM; Cilense, M.; Zaghete, M. A.; Stojanovic, B. D.; Varela, José Arana [UNESP] (Elsevier B.V., 2002)
PLZT thin films were prepared by a dip coating process using Pechini's method, also known as polymeric precursor method. The PLZT solution was obtained from a mixture of the individual cation solutions and the process to prepare each solution is based on metallic citrate polymerization. The viscosity of the PLZT solution was adjusted at 40 cP while the ionic concentration was adjusted at 0.1 M. PLZT solutions were deposited on silicon (100) and platinum coated silicon (100) substrates with withdrawal speed at 5 mm/min. The coated substrates were thermally treated with a heating rate of 1 degreesC/min up to 300 degreesC and 5 degreesC/min up to 650 degreesC in order to obtain homogeneous and cracks free films. The influence of oxygen flow on crystallization and morphology of PLZT (9/65/35) thin film is discussed. (C) 2002 Elsevier B.V. Ltd and Techna S.r.l. All rights reserved.
Keywords: films; electron microcospy; surfaces; X-ray methods; PLZT